Sei sulla pagina 1di 13

P 0 , P 1 ,

, P h (h + 1) E n

h E h

P

P ∈ E h ⇐⇒ P = P 0 +

h

k =1

λ k (P k P 0 )

λ k R k = 1 ,

, h h (λ k ) k =1,

,h

P E h P 0

P 1 ,

, P h

P

E h

P = 1

h

k

=1

λ k P 0 + λ 1 P 1 +

+ λ h P h

h

h

λ 0 := 1 λ k P = λ k P 0

k

=1

k

=0

(h + 1) ( λ 0 , λ 1 ,

, λ h )

h

k =0

λ k = 1

P 0 , P 1 ,

, P h (h + 1) E n

h s h P 0 , P 1 ,

, P h

E h λ k P k

h s h P 0 , P 1 ,

, P h

E h λ k P k

h

P 0

s 1 1

P 0 , P 1 E n

r s 1 P 0 , P 1

P 0 , P 1 s 1 = s 1 ∪ {P 0 , P 1 } P 0 , P 1 , P 2

E n P 0 , P 1 , P 2

P 0 , P 1 , P 2 P 0 , P 1 , P 2 , P

E n s 3 P 0 , P 1 , P 2 , P

P =

h

k=0

λ k P k P 0 , P 1 ,

, P h (h + 1)

h

E n λ k = 1 P

k=0

λ k k = 0,

, h P 0 , P 1 ,

, P h

P 0 , P 1 ,

, P h

E n E h

s h

E h

s h

E n

E 1 k = 0 ,

h

(

k )

, h E h

h h + 1

E h A E h k = 0 ,

1

A

2

(

k )

(

k )

, h

h + 1 E

(

k )

h

(

h

k )

(

1

k )

A s h = A

1

1

k =0

E h E h s h E n

E n

h

k =0

C k C k = A

(

1

k )

∪ E

(

h

k )

1 k = 0 ,

, h

k = A ( 1 k ) ∪ E ( h k ) − 1 k

E n h + 1

P 0 , P 1 ,

, P h s h E n

n > h E 3 P 0 P 1 s 1

E 3 3

P 0 , P 1 ,

E n

, P h

s h P 0 , P 1 , , P h

s h

P, Q s h

d(P, Q ) = P 0 + =1 λ k (P k P 0 ) P 0 + =1 µ k ( P k P 0 )

h

k

h

k

=

=1 ( λ k µ k ) ( P k P 0 )

h

k

h

=1 | λ k µ k | P k P 0 .

k

sup

P,Qs h

h

d(P, Q ) =1 d (P k , P 0 )
k

λ k , µ k [0 , 1]

sup d(P, Q ) s h

P,Qs h

∈ [0 , 1] sup d ( P, Q ) s h P,Q ∈ s h

s h P 0 , P 1 ,

s h

, P h s h

P s h P

(0 ,

, λ i ,

λ j ,

, 0)

λ i , λ j > 0 i

= j ε > 0

A B (0 ,

, λ i + ε,

, λ j ε,

(0 ,

, λ i ε,

, λ j + ε,

, 0) s h

, 0)

P A B

h

E n

, λ j + ε, , 0) s h , 0) P A B h −

s h s h P 0 , P 1 , , P h

A B s h A =

λ k µ k > 0 k = 0 ,

h

h

k

=0

h

λ k P k B =

λ k = 1

h

h

k =0 µ k P k

µ k = 1

k

=0

k

=0

P AB P = tA + (1 t )B t [0 , 1]

P = t

h h

k

=0

λ k P k + (1 t )

k

=0

µ k P k =

h

k

=0

[ k + (1 t )µ k ] P k

P P 0 , P 1 ,

, P h

k + (1 t )µ k > 0

h

k =0

k + (1 t )µ k = 1 s h

s h

k =0 tλ k + (1 − t ) µ k = 1 s h s

s h

h >

0

P 0 ,

, P h s h P Q

s h d ( P, Q )

Q

AB s h P Q AP B

d (P, Q ) < d ( P, B )

P Q

s h

AB s h P Q AP B d ( P, Q ) < d ( P,
AB s h P Q AP B d ( P, Q ) < d ( P,

E n

s h P 0 , P 1 ,

, P h

s h s h s h

s h proprie

h h P 0 , P 1 ,

, P h

s k s t

s k s t

s h

s 1 s h h 1

K E n

s K t s t K

K

K

K

K s

sK

K | K |

K

| K |

K P | K |

K

P h K

| K | h

K K s s ∈ K K | K | K | K | K P

K K s s ∈ K K | K | K | K | K P

E 3

K K 0

K K 0 K 0 K

| K 0 | | K | K 0 K 1 K

K 0 K 1 K 0 K 1

K

K X

K

X

K h scheletro K

K K h

0 K

V (K )

K K

V 1 V 2 K V 1

V 2 K V 1 V 2

K | K |

P Q | K | , s t

P Q

P s Q

t K

| K | , s t P Q P s Q t K K | K

K | K |

| K | K

K | K |

V K X 1 | K |

K

V P X 1 s

X 1 s X 1

V

| K | X 1

X 2 X 1 | K |

| K | K

V P X 2 t

X 2 t

X 2 X 1 X 2 = | K |

X 1 X 2 = | K |

P ∈ X 2 t X 2 t X 2 X 1 ∪ X 2 =

K

| K |

E n

X E n X

X

Γ E 2

Γ

S

O

O

E n cono

X E n P

X X P

Γ P (X E n X P

X

h s h P 0 ,

, P h

j = 1 ,

, h

s 0 = { P 0 }

s j =

Γ P j (s j 1 )

s h h E n P 0 ,

P h

h σ h s h

σ h

1 σ 1 = (P 0 P 1 )

P 0 P 1 2 σ 2 = ( P 0 P 1 P 2 )

σ h = (P 0

P h ) h E n (h

1) P i

P 0

ˆ

P

i

P h := (P 0

P i 1 P i+1

h )

P

σ h i

i (h 1)

σ h

K

E n

| K |

K

K

| K |

K K

| K | = | K | V (K ) K

K B i 0 ,

B

i h B i 0 , h i

,i

1

h

+1

=0 λ j,k k =0,

h

j

,h

λ j,k

k j B i 0 , h

,i

B i 0 ,

B i h

B i 0 ,

, B i h

V V (K )

K = { B 0 , B 1 , B 2 , B 3 , l 0, 1 , l 0, 2 , l 1, 2 , l 2, 3 , T } | K |

V (K ) = { B 0 , B 1 , B 2 , B 3 } V = V (K ) ∪ {B 0, 1, 2 , B 0, 1 , B 0, 2 , B 1, 2 , B 2, 3 }

{B 0, 1, 2 , B 0, 1 B 0, 2 } { B 0, 1, 2 , B 0, 1 B 2, 3 }

K V (K ) V ′
K
V (K )
V ′

V (K )

K

V K

| K | = | K |

K ′′ , K ′′′ ,

,

K ( r ) ,

h

s h P 0 ,

, P h

s h

s h

s h

K E n

K K

K

K E n µ (K ) K

1 K

K

+1 µ (K ) K

m

m

K

m

µ (K )

K ε

r

µ K ( r ) < ε

K | K |

| K | E n

| K |

| K |

| K | | K |

K, L

ϕ : V ( K ) V (L ) K

L ϕ

ϕ X V (K )

K L

K L

ϕ :

V (K )

V (L )

ϕ˜ : | K | → | L | K L

P ∈ | K | s h P =

h

j =0

λ j V j V j j = 0 ,

, h s h ϕ k : s h → | L |

Q s h ϕ k (Q ) =

h

=0 λ j ϕ ( V j )

j

ϕ k

{ϕ t } K | L |

ϕ k ϕ

ϕ˜ : | K | → | L |

{ϕ t }

k { ϕ t } K | L | ϕ k ϕ ϕ ˜ : |

ϕ˜ : | K | → | L |

| K | | L |

f : | K | → | L |

( X, d)

U

= { U i } iI

λ Y X λ

U λ

U

U X x X

U i U U i r x > 0

D ( x, r x ) U i D = D x, r 2 x x X

X X

D D x i , r i

2 i=1,

,n

X

λ = min x X D (x, λ)

1in

r

i

2

U

λ

λ x X 1 j n x D x j , r 2 j

D ( x j , r j )

U r U D ( x, λ) D (x j , r j )

z D (x, λ)

d ( x j , z ) d (x, z ) + d (x, x j ) < λ + r j

2 r j

z ) + d ( x, x j ) < λ + r j 2 ≤

K s

st K (s ) s K s

s st K (s )

st K (s ) K K 0

K s K 0 st K 0 (s ) st K ( s )

st (s ) st K (s )

K s

| st K (s )| | K | st K (s )

V K | st K (V )|

K V

K s

st K ( s )

| K |

K \ st (s ) s

t s t

K \ st (s ) K

| K \ st (s )| | K | | K |

| K \ st (s )| = | K | \ | st (s )|

| st (s )| | K |

= | K | \ | st ( s ) | | st ( s )

V 1 , V 2 ,

V h

K

K

V 1 , V 2 ,

V h s K s

st

(V i )

i = 1 ,

h

, h s ⊆ | st (V i )| x

i=1

s x st (V i ) i = 1 ,

h

i=1 | st (V i )|

, h

V 1 , V 2 ,

V h s

i =1 | st ( V i ) | , h V 1 , V 2

f : | K | −→ | L |

˜

E n f : | K | −→ | L |

˜

f x ∈ | K | f ( x)

f (x)

K L

f

: | K | −→ | L |

r 0

˜

f

:

K ( r ) −→ | L |

f

V (L ) = {W 1 ,

, W m } L

{| st L ( W j )|} j =1, | L |

,m

f F = f 1 (| st (W j ) | ) j =1,

,m

| K | λ

r 0 µ K ( r ) < λ

2

V K ( r ) = { V i ,

, V n } K (r )

| st K (r) (V i )| λ V i i = 1 ,

2

| st (V i ) | λ i = 1 ,

m | st (V i )| ⊆ f 1 st W j ( i)

, n

, n 1 j (i )

K (r ) L

V i K (r ) j (i )

˜

f (V i ) =

W j ( i)

˜

f : V K (r ) −→ V ( L )

V 1 ,

, V h K ( r )

h

i=1

| st (V i )| =

f i=1 | st (V i )|

h

h

i=1

f ( | st (V i )| ) =

˜

h

f i=1 f ( | st (V i )| )

h

i=1

st f (V i )

˜

˜

f (V i ) i = 1 ,

, n L

˜

f

K (r )

| L |

˜

f f

x ∈ | K | V 1 ,

, V k x K (r )

x ∈ | st (V i )| i = 1 ,

, k

f (x)

k

f

i=1

(| st (V i )| )

k

i=1

st f (V i )

˜

 

˜

f (x) L

f (V i ) i = 1 ,

, k

 

˜

f

( x)

˜

) i = 1 , , k   ˜ f ( x ) ˜ f :

f : | K | −→ | L | f

˜

f f

F : ( x, t ) ∈ | K | × I −→ f ( x ) t + (1 t )

˜

f ( x) ∈ | L |

f

f : | K | −→ | L | x ∈ | K |

f (x) = W L W

f (x) =

˜

f (x) f

f L K

f : | K | −→ | L |

f f

L

f f d | L | f (x), f (x) x ∈ | K |

˜

˜

(X, d X ) (Y, d Y )

X Y X X

Y f

g Y X d(f, g ) := inf

x

X d Y ( f (x) , g ( x))

Y X , d

ϕ :

K ( r ) −→ L ( s)

r s

|

L | | K |

f : S 1 −→ S 2

S 1 S 2

S 1

S 2

˜

f f

S 1

˜

f

˜

P S 2 f

S 1 f S 1 S 2 \ {P } f

˜

˜

f

S 2 \ {P } R 2